Quantitative expression of human drug transporter proteins in lung tissues: Analysis of regional, gender, and interindividual differences by liquid chromatography–tandem mass spectrometry. Issue 9 (13th May 2013) - Sakamoto, Atsushi; Matsumaru, Takehisa; Yamamura, Norio; Uchida, Yasuo; Tachikawa, Masanori; Ohtsuki, Sumio; Terasaki, Tetsuya; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract The purpose of the present study was to clarify the expression levels of transporter proteins in human lung tissue and to analyze regional and interindividual differences in primary cultured epithelial cells. Organic cation/carnitine tranporter 1 (OCTN1) protein expression was highest (2.08 ± 1.19 fmol/μg protein) in human lung tissue, followed by multidrug resistance‐associated protein 1 (MRP1) and breast cancer resistance protein expression (1.41 ± 0.41, 1.30 ± 1.29 fmol/μg protein, respectively). Interestingly, the same expression levels of OATP2B1 protein were demonstrated among the epithelial cells derived from all pulmonary regions for the first time. These results suggest that OCTN1 may be the best target transporter protein for pulmonary disease drug design, and OATP2B1 may be an alternative target. MRP1 protein expression was also high and mainly localized in bronchial and alveolar regions. Regarding interindividual differences, the MRP1 protein showed a significant 18‐fold maximal difference in the bronchial region among five donors. Sixteen of the 18 transporters showed higher expression in female lungs than in male lungs, especially MRP8 showed a 7.32‐fold maximal difference. In conclusion, the protein expression profiles of pulmonary drug transporters and regional, gender, and interindividual differences were clarified. These findings may provide significant insights for pulmonary disease drug design and indicate that administration by inhalation may be viable. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3395–3406, 2013